Improvement Soot Particles Separation Equipments for Rubber Smoking Chamber - Wachara Kalasee (My University, 2009)
Soot produced from rubber tree wood combustion during the process of drying natural rubber sheets has been shown to produce negative health effects for workers, as well as poorer quality rubber sheets. This study examined ways to improve soot particle separation equipment for rubber smoking chambers. An impaction wall was able to catch all soot particles ranging in size from 3.3-4.7 microns and a modified electrostatic precipitator, installed outside of the rubber smoking chamber in order to decrease danger to workers and with the highest available voltage supply of 12 kV, captured soot particles 0.43-3.3 microns in size. This modified precipitator operated longer than the usual time 120 hours or more before requiring cleaning; equivalent to smoking about 12 lots of rubber sheets or operating for 3 months during high rubber production season. The total efficiency of soot particle separation through the use of the modified collection equipment was more than 50% for all tests. In addition, the color index of rubber sheets used in the testing improved from 6.0 to 12.0. Coloration, which is a measure of quality, was better than sheets from smoking chamber lacking soot particle separation equipment.
Keywords: Electrostatic precipitator; Particle (ecology); Aerosol Filtration and Electrostatic Precipitation